How do you solve -2(x + 3) = -2(x + 1) - 4? Algebra Linear Equations Equations with Variables on Both Sides 1 Answer Mia Sep 7, 2017 x can be any real number " " x in RR Explanation: -2 (x+3) = -2 (x+1) -4 " " rArr-2×x-2×3 = -2×x-2×1-4 " " rArr-2x-6 = -2x-2-4 " " rArr-2x-6 = -2x-6 " " rArr-2x+2x = -6+6 " " rArr0.x = 0 " " x can be any real number " " therefore x in RR Answer link Related questions How do you check solutions to equations with variables on both sides? How do you solve 125+20w-20w=43+37w-20w? How do you solve for x in 3(x-1) = 2 (x+3)? Is there a way to solve for x without using distribution in 4(x-1) = 2 (x+3)? How do you solve for t in 2/7(t+2/3)=1/5(t-2/3)? How do you solve 5n + 34 = −2(1 − 7n)? How do you simplify first and then solve −(1 + 7x) − 6(−7 − x) = 36? Why is the solution to this equation -15y + 7y + 1 = 3 - 8y, "no solution"? How do you solve for variable w in the equation v=lwh? How do you solve y-y_1=m(x-x_1) for m? See all questions in Equations with Variables on Both Sides Impact of this question 1676 views around the world You can reuse this answer Creative Commons License